Protein C Gene Mutation in an Older Adult Patient with Clostridium perfringens Septicemia-Related Visceral Vein Thrombosis - Kanosue, Kiyoko; Nagaya, Satomi; Morishita, Eriko; Yamanishi, Masayoshi; Imashuku, Shinsaku (TH Open, 2021)
A 78-year-old Japanese male with Clostridium perfringens septicemia and cholecystitis was found to have thrombosis in the left branch of intrahepatic portal vein as well as superior mesenteric vein. Visceral vein thrombosis (VVT) in this case was associated with protein C deficiency, due to a heterozygous mutation, p. Arg185Met. Our experience emphasizes that VVT, or other thromboembolic events, may occur in later life, triggered by environmental thrombosis risk factors, together with underlying hereditary protein C gene mutation.
Keywords: visceral vein thrombosis; protein C deficiency; Clostridium perfringens; septicemia; older adult